2016
DOI: 10.1523/jneurosci.0085-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Ensheathing Cell Transplantation after a Complete Spinal Cord Transection Mediates Neuroprotective and Immunomodulatory Mechanisms to Facilitate Regeneration

Abstract: Multiple neural and peripheral cell types rapidly respond to tissue damage after spinal cord injury to form a structurally and chemically inhibitory scar that limits axon regeneration. Astrocytes form an astroglial scar and produce chondroitin sulfate proteoglycans (CSPGs), activate microglia, and recruit blood-derived immune cells to the lesion for debris removal. One beneficial therapy, olfactory ensheathing cell (OEC) transplantation, results in functional improvements and promotes axon regeneration after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
114
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 47 publications
5
114
0
Order By: Relevance
“…6H. [Color figure can be viewed at wileyonlinelibrary.com] OEC transplantation has emerged as a very promising experimental therapy to treat the axonal injuries of central nervous system (Cao et al, 2004;Chiu et al, 2009;Khankan et al, 2016;Li et al, 1998;Mackay-Sim and St John, 2011;Raisman and Li, 2007;Ramon-Cueto et al, 1998;Su and He, 2010). (n 5 13, 16, 12, 9, 12, 8 cells in the indicated groups, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6H. [Color figure can be viewed at wileyonlinelibrary.com] OEC transplantation has emerged as a very promising experimental therapy to treat the axonal injuries of central nervous system (Cao et al, 2004;Chiu et al, 2009;Khankan et al, 2016;Li et al, 1998;Mackay-Sim and St John, 2011;Raisman and Li, 2007;Ramon-Cueto et al, 1998;Su and He, 2010). (n 5 13, 16, 12, 9, 12, 8 cells in the indicated groups, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The [Ca 21 ] i was determined by the ratio of Fluo-4 and Flura-Red fluorescence. (C) Summary of average peak levels of Ca 21 signal based on the max [Ca 21 ] i signal from individual cells in the soma under various conditions (n 5 13, 16, 12, 9, 12, 8 cells OEC transplantation has emerged as a very promising experimental therapy to treat the axonal injuries of central nervous system (Cao et al, 2004;Chiu et al, 2009;Khankan et al, 2016;Li et al, 1998;Mackay-Sim and St John, 2011;Raisman and Li, 2007;Ramon-Cueto et al, 1998;Su and He, 2010). Organized migration of OECs enhances the axon regeneration (Chehrehasa et al, 2010;Ekberg et al, 2012;Windus et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, there do exist effective bridging techniques that have been used to span larger lesions (Houle et al, 2006;Alilain et al, 2011;Lee et al, 2013;Tabakow et al, 2014). Importantly, the addition of strategies that manipulate the astrocyte scar interface at the ends of the bridge and that take advantage of the plasticity of the reactive astrocyte must be employed to allow axons to regenerate not only into but well beyond the lesion Khankan et al, 2016). We have learned over the past decade or so that the glial scar is a lot more than just astrocytes and with this new knowledge our views about regeneration failure have evolved considerably (Cregg et al, 2014).…”
mentioning
confidence: 99%
“…Mature OECs expressing the neurotrophin receptor p75 NTR have been shown to increase neurite outgrowth significantly in brain slices (Jiao et al ., ). It has also been suggested that mature OEC expressing p75 NTR increased the total neurites length of cortical neurones in culture by providing both an adhesive cellular substrate and permissive soluble factors (Khankan et al ., ). In line with our research, this latter study demonstrated a correlation between OEC process alignment with neurites and the size of neurite elongation, and it suggested that OEC process alignment was a method for OEC to enhanced neurites elongation/outgrowth.…”
Section: Discussionmentioning
confidence: 97%